The Regulation of Human Muscle Stem Cells in Response to Muscle Damage and Aging - McKay, Bryon R. (My University, 2011)
Skeletal muscle exhibits a remarkable capacity for growth and regeneration in response to physiological stimuli. This extensive plasticity is, in part, due to a tissue-resident stem cell called the satellite cell. Satellite cells respond to myotrauma by upregulating a class of transcriptional networks which orchestrate myogenic specification. This process is controlled by four main transcription factors known as the myogenic regulatory factors: Myf5, MyoD, MRF4 and Myogenin. Satellite cells respond to molecular cues released from the muscle fiber or inflammatory cells in response to muscle damage. Although several regulators have been implicated in the control of the satellite cell response to exercise or damage, very few of these have been examined in humans. Insulin-like growth factor-1 (IGF-1) and Interleukin-6 (IL-6) have been demonstrated to enhance satellite cell proliferation in animal and cell culture models. IGF-1 has also been shown to induce myogenic differentiation, however little is known about IGF-1 and IL-6 in humans, in response to physiological levels of muscle damage. Myostatin has been identified as a negative regulator of muscle growth and an inhibitor of satellite cells in mice. To date no data exists regarding the relation of myostatin to the satellite cell response to exercise and in the context of aging. The work outlined in this thesis provides support for the proposed divergent effects of the IGF-1 splice variants on satellite cell function. IGF-1 appears to be preferentially spliced as IGF-1Ec during the proliferative phase of the myogenic program while IGF-1Ea and Eb appear as the predominant splice variants during the initiation of differentiation based on the expression of the MRFs. Furthermore, the localization of IGF-1 with Pax7 in muscle-cross sections in the post-exercise time-course lends support to the importance of IGF-1 in the myogenic response to myotrauma. This thesis also provides novel evidence to support the role of IL-6 in the regulation of satellite cell proliferation in response to acute muscle damage in humans. These data confirm that IL-6 imparts its action on the satellite cell via the JAK2/STAT3 pathway. In addition, for the first time, myostatin is demonstrated to be altered by acute exercise in both young and older adults and this effect is most notable in the satellite cell compartment. In addition, these data implicate myostatin as a contributing factor to age-related satellite cell dysfunction in response to exercise (or myotrauma).
Keywords: Muscle Stem Cells; Human; Exercise; Aging; Satellite Cells; Myostatin; Exercise Science; Exercise Science